The Effect of Competence on Employee Performance and Organizational Commitment as a Mediation Variable (Empirical Study at the Office of PT PLN (Persero) Parent Unit for Papua and West Papua) - Mario Marudut Sirait; Suratini Suratini; Sjamsier Husen; Abdul Rasyid; Fahcruddin Pasolo (Budapest International Research and Critics University, 2022)
The purpose of this study was to determine the effect of Competence Against Employee Performance and Organizational Commitment as Mediation Variables (Empirical Study at the Office of PT PLN (Persero) Parent Unit for Papua and West Papua). In this study the method used is the type of research used in this study is a type of quantitative research with a causal method or approach. Data collection techniques were carried out using questionnaires, using sources from previous research and the method of observation or direct observation. The analysis that will be used by the author is quantitative, using a sample of 200 people from 1266 people at the Office of PT PLN (Persero) the Main Unit for Papua and West Papua. Data analysis using IBM SPSS AMOS 22 and Sobel. The results of this study indicate that employee competence has a positive and significant impact on organizational commitment at the PT PLN (Persero) UIW Papua and West Papua Offices. And employee competence indirectly affects employee performance through organizational commitment at the PT PLN (Persero) Office of UIW Papua and West Papua.